2017
DOI: 10.1158/1055-9965.epi-16-0886
|View full text |Cite
|
Sign up to set email alerts
|

Measured Adiposity in Relation to Head and Neck Cancer Risk in the European Prospective Investigation into Cancer and Nutrition

Abstract: Background Emerging evidence from cohort studies indicates that adiposity is associated with greater incidence of head and neck cancer (HNC). However, most studies have used self-reported anthropometry which is prone to error. Methods Among 363 094 participants in the European Prospective Investigation into Cancer and Nutrition study (EPIC) with measured anthropometry, there were 837 incident cases of HNC. HNC risk was examined in relation to body mass index (BMI) [lean: < 22.5 kg/m2, normal weight (referenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“… 19 , 33 Some discrepancies for hip size may also be due to the mutual adjustment used in previous studies for HC and WC, which are correlated strongly with each other and, as explained above, are both proxy measures of total body size. Thus, we could not confirm a reported inverse association of HC adjusted for WC with head and neck cancer in men, 25 although our results were directionally consistent in women, but found an inverse association of HI with liver cancer, not reported for HC adjusted for WC. 29 Further, we could not confirm a reported inverse association of HC adjusted for body weight with RCC in men, 34 but found evidence for an inverse association of HI with clear‐cell adenocarcinoma, especially in women.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 19 , 33 Some discrepancies for hip size may also be due to the mutual adjustment used in previous studies for HC and WC, which are correlated strongly with each other and, as explained above, are both proxy measures of total body size. Thus, we could not confirm a reported inverse association of HC adjusted for WC with head and neck cancer in men, 25 although our results were directionally consistent in women, but found an inverse association of HI with liver cancer, not reported for HC adjusted for WC. 29 Further, we could not confirm a reported inverse association of HC adjusted for body weight with RCC in men, 34 but found evidence for an inverse association of HI with clear‐cell adenocarcinoma, especially in women.…”
Section: Discussioncontrasting
confidence: 99%
“…The main compatibilities between our findings and previous reports concern cancers associated more strongly with waist size. Thus, positive associations based on WC or WHR, with or without adjustment for BMI and in some studies for HC, have previously been reported for cancers of the head and neck, 23 , 24 , 25 esophagus and gastric cardia (adenocarcinoma), 21 , 24 , 26 colon, 24 , 27 , 28 liver, 24 , 29 lung overall, 30 and bladder (men). 24 , 31 , 32 Nevertheless, while we observed comparable associations with ABSI and WHI, previous studies have often reported positive associations with WC but not with WHR adjusted for BMI.…”
Section: Discussionmentioning
confidence: 77%
“…Eight studies reported the association between BMI (n= 2,859 cases) and risk of HNC 11,12,[14][15][16][54][55][56] , with 15 studies reporting the association with type 2 diabetes (n= 17,582 cases) 12,[17][18][19][20]23,24,[57][58][59][60][61][62][63][64] , six studies hypertension (n= 12,151 cases) 12,[19][20][21][22][23] , and four studies dyslipidaemia (n= 6,410 cases) 12,19,20,65 and HNC risk (Table 2). Adjustments were made for potential confounders of two or more factors, including age, in all studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the largest pooled analysis, obesity defined by higher BMI was associated with a protective effect for HNC in current smokers (hazard ratio (HR)= 0.76, 95%CI (0.71, 0.82), p <0.0001, per 5 kg/m 2 ) and conversely, a higher risk in never smokers (HR= 1.15, 95%CI (1.06, 1.24) per 5 kg/m 2 , p <0.001) 11 . More recent cohort studies have failed to show a clear association between BMI and HNC [12][13][14][15][16] . Similarly, a meta-analysis of observational studies investigating type 2 diabetes with oral and oropharyngeal subsites found an increased risk ratio (RR) of 1.15, 95%CI (1.02, 1.29) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, a greater waist circumference (WC) (HR⍰ ⍰1.04, 95%CI 1.03–1.05 per 5⍰cm, p ⍰< 0.001) and waist-to-hip ratio (WHR) (HR⍰1.07, 95%CI 1.05–1.09 per 0.1 unit, p < 0.001) were associated with increased HNC risk, which did not vary by smoking status (Gaudet et al, 2015). However, more recent cohort studies have failed to show a clear association between BMI and HNC (Cao et al, 2020; Diaz et al, 2021; Gribsholt et al, 2020; Jiang et al, 2021; Ward et al, 2017). A meta-analysis of observational studies investigating T2D with oral and oropharyngeal subsites, showed an increased risk ratio (RR) of 1.15, 95%CI 1.02–1.29, P heterogeneity = 0.277 (Gong, Wei, Yu, & Pan, 2015), a result which is consistent with more recent independent cohorts (Jiang et al, 2021; H.-B.…”
Section: Introductionmentioning
confidence: 99%